AN EXPERIMENTAL INVESTIGATION OF THE EFFECT OF NATURAL FIBER TREATMENT AND MARINE ENVIRONMENT ON CANNABIS SATIVA/EPOXY LAMINATES - CHETHAN, K N; Hegde, Sharun; Kumar, Rajesh; N H, Padmaraj (Journal of Applied Engineering Science, 2021)
Materials have helped in evolving technology to a great extent. Composites have replaced conventional metals/non-metals because of their lightweight. Natural Fibres have been need of the hour owing to environmental concerns and ease of availability. In this work, Cannabis Sativa fibers were treated with 5% Potassium Hydroxide solution. The laminates were prepared by the Compression Moulding technique by reinforcing treated and untreated fibers with an epoxy matrix material. To access the durability of natural fiber composites in the marine environment, prepared laminates were aged in seawater for 150 days. Tensile, flexural and moisture absorption behavior tests have been performed to estimate the durability in seawater. The data obtained have been compared with pristine treated and untreated fiber reinforced samples. From the results, it has been observed that tensile and flexural behavior of untreated fiber reinforced composites were superior to a treated counterpart in both pristine and aged conditions.
Keywords: treated, untreated, ageing, sea-water, modulus